Mental Health among Automobile industry workers in Chennai – A Cross-sectional study from a Single Industrial unit (International Journal of Occupational Safety and Health, 2023)
Introduction: Working in a mentally healthy place is necessary for people. Adverse mental health conditions can lead to disruption in work which in turn causes absenteeism, low productivity, and financial constraints. This study intends to assess the levels of depression, anxiety and stress and to determine its associated factors among the workers in the automobile industry in Chennai.Methods: A cross-sectional study was conducted among 227 Automobile industry workers in Chennai, India. A semi-structured questionnaire was used to collect information about the socio-demographic and working details of the study subjects, while the Depression Anxiety Stress Scale (DASS -21) was used to assess mental health status. Descriptive variables were expressed as proportions, while Pearson's Chi-square test was used to study the association between dependent and independent variables.Results: A total number of 227 participants were included in the study. More than 80 % of the workers were permanent employees. The prevalence of Depression, anxiety and stress among the study subjects are 38.8%, 43.6 % and 26.9 %, respectively. Workers in the middle age group of 30- 39 years had a higher risk of developing depression, anxiety, and stress than those in the other age groups. For Depression, age, type of family, employment status, and working experience were statistically significant (p